Improving Badminton Player Detection Using YOLOv3 with Different Training Heuristic - Haq, Muhammad Abdul; Tagawa, Norio (Society of Visual Informatics, 2023)
There has been a considerable rise in the amount of research and development focused on computer vision over the previous two decades. One of the most critical processes in computer vision is